What makes regions in Eastern Europe catching up? The role of foreign investment, human resources and geography - Gabriele Tondl; Goran Vuksic (Rheinische Friedrich-Wilhelms-Universität Bonn, Zentrum für Europäische Integrationsforschung (ZEI), 2003)
This paper analyses regional growth in Eastern Europe in the second half of the 1990s, when regional disparities sharply increased. We aim to identify the factors behind growth and investigate in particular the role of (foreign) investment, education and innovation as well as geographical factors in a model of economic growth. The key relationships are estimated with spatial econometric tools on empirical data for the period 1995-2000. We find that foreign direct investment was paramount for growth in that period. EU border regions and capital areas clearly outperformed others. Further, regional growth clusters have appeared. Surprisingly, the high level of secondary education played no role to growth. Higher education, in contrast, was important, also for technology transfer.
Keywords: R11; P25; C21; F15; 330; Regional growth; Eastern Europe; foreign direct investment; education; spatial econometrics; Regionales Wachstum; Regionale Entwicklung; Entwicklungskonvergenz; Direktinvestition; Humankapital; Geo